Industrial refrigeration handbook - Stoecker, W. F. (Wilbert F.) (McGraw-Hill, 1998)
Offers coverage of the fundamentals, design, installation, and operation of industrial refrigeration systems. This book details the industry changes caused by the conversion from CFCs to non-ozone-depleting refrigerants and by the development of microprocessors and secondary coolants.